2011
DOI: 10.1146/annurev.physchem.012809.103503
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation and Allied Dynamics in Water and Aqueous Solutions

Abstract: The reorientation of a water molecule is important for a host of phenomena, ranging over--in an only partial listing--the key dynamic hydrogen-bond network restructuring of water itself, aqueous solution chemical reaction mechanisms and rates, ion transport in aqueous solution and membranes, protein folding, and enzymatic activity. This review focuses on water reorientation and related dynamics in pure water, and for aqueous solutes with hydrophobic, hydrophilic, and amphiphilic character, ranging from tetra-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
502
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(525 citation statements)
references
References 144 publications
19
502
3
1
Order By: Relevance
“…We recognize that n k⊥ (t) undergoes librational motions and C ⊥ (t) decays on a timescale of 0.01 ps with a minimum at t = 0.023 ps. In liquid water, similar short-time behaviors with local minimum and maximum have been observed in various time-dependent quantities in simulations and experiments as manifestation of librational motions [38][39][40][41] .…”
Section: Orientation Time-correlation Functionssupporting
confidence: 70%
“…We recognize that n k⊥ (t) undergoes librational motions and C ⊥ (t) decays on a timescale of 0.01 ps with a minimum at t = 0.023 ps. In liquid water, similar short-time behaviors with local minimum and maximum have been observed in various time-dependent quantities in simulations and experiments as manifestation of librational motions [38][39][40][41] .…”
Section: Orientation Time-correlation Functionssupporting
confidence: 70%
“…The resolution of this claim, however, depends on the water mode probed by the observations. There is a relatively insignificant slowing down of water's single-molecule rotational dynamics in hydration shells [67]. An attempt to find a separate dynamic process in density fluctuations (translations) probed by depolarized light scattering resulted in the realization that cross protein-water correlations, instead of a separate dynamic process, can explain the data [68].…”
Section: Discussion and Implications For The Protein Dynamical Trmentioning
confidence: 99%
“…hydrophobic hydration | hydrogen bonding | IR spectroscopy | electrostatic screening | ab initio molecular dynamics D espite its great importance in numerous phenomena, the origin of hydrophobicity remains one of the most disputed topics in science (1)(2)(3)(4)(5). Experimental studies have shown that small purely hydrophobic solutes (alkanes and noble gases) in water increase the order (6,7) and restrict the mobility (8) of neighboring water molecules.…”
mentioning
confidence: 99%
“…Neutron diffraction (11,12) and extended X-ray absorption fine structure (EXAFS) (13) studies, however, show that the water molecules around small purely hydrophobic molecules do not differ significantly from those in pure liquid water. According to the dynamic view, the hydrophobic solute causes slowdown of the dynamics of the nearby water molecules by obstructing the jump mechanism of rotational relaxation, whereas water structure and H-bonding strength remain basically unchanged (5,14). The main problem of these two views is that there is essentially no direct experimental support for enhanced H bonding and resulting formation of icebergs in the hydration shell of small purely hydrophobic solutes (15) or a jump mechanism of rotational relaxation of the water molecules (5).…”
mentioning
confidence: 99%